Memory, Archives of Resistance, and the Role of CAMeNA: Interview with Beatriz Torres Abelaira - LUQUE BRAZÁN , José Carlos; DE LA O DE LA CRUZ, Fabiola (Utopía y Praxis Latinoamericana, 2025)
This article presents an interview with Beatriz Torres Abelaira, a Chilean exile and founder of the Centro Académico de la Memoria de Nuestra América (CAMeNA) at the Universidad Autónoma de la Ciudad de México (UACM). The conversation traces her biography, marked by the 1973 Chilean coup d'état, her exile, arrival in Mexico, and her work in recovering, organizing, and disseminating archives related to historical memory and human rights struggles in Latin America. Torres recounts the acquisition of the Gregorio Selser archive as the cornerstone of CAMeNA, as well as the incorporation of emblematic collections such as those of General Gallardo, Ernesto Capuano, Sergio Méndez Arce, the Comité ¡Eureka!, and various LGBT archives. The text highlights memory as a political battleground and a tool of resistance against silences imposed by authoritarian regimes and limited democratic transitions. It also reflects on the importance of guaranteeing free access to archives, understood as instruments of truth and justice, and of preserving a documentary heritage that contributes to building a history narrated from the voices of the oppressed.